Identification and characterization of a naïve CD8+ T cell repertoire for benzylpenicillin. Issue 5 (8th February 2019) - Bechara, Rami; Maillere, Bernard; Joseph, Delphine; Weaver, Richard J.; Pallardy, Marc
Summary: Background: Beta‐lactams allergy is the most commonly reported drug allergy and constitutes an important health problem. We previously showed the pre‐existence of a naïve CD4+ T cell repertoire for benzylpenicillin (BP) coupled to human serum albumin (HSA) but little is known about the naïve CD8+ T cell repertoire specific for BP. Objective: The purpose of this work was to identify naïve CD8+ T cells specific for BP and to explore mechanisms dictating their activation. Methods: Co‐cultures were established with naïve CD8+ T cells and autologous dendritic cells (DCs) loaded with HSA‐BP or free BP. T cells were restimulated once a week with autologous DCs loaded with HSA‐BP or BP. The specific CD8+ T cell response was measured using an IFN‐γ ELISpot assay. Results: When using free BP, we were able to detect a naïve CD8+ T cell repertoire for BP in the 6 out of 7 tested healthy donors. However, our results showed that HSA‐BP was recognized by naïve CD8+ T cells in only one donor out of five tested healthy donors. Using free BP, we evidenced its binding to cellular proteins in DCs that was concentration dependent and was correlated with BP‐specific CD8+ T cell activation. Moreover, the BP‐specific CD8+ cell response was MHC class I‐dependent and required intracellular processing and proteasome activity. Conclusion and clinical relevance: This work showed the existence of a naïve CD8+ T cell repertoire for BP when DCs were treated with free BP suggesting that patients could be immunized by haptenated peptides from cellular proteins generated in antigen‐presenting cells.